IMPROVING THE CHANGE-MANAGEMENT PROCESS. - Mohan, Kannan; Peng Xu; Ramesh, Balasubramaniam (Communications of the ACM, 2008)
The article discusses the use of software configuration management to improve the change-management process. According to the author, one of the most common reasons for the failure of software development projects is the continuous evolution of software caused by volatility in customer requirements. Sources of this volatility are diverse, ranging from changes in technology, end-user needs, and dynamic market pressures. The author examines the ways software configuration management can mitigate problems related to these failures. INSET: HOW THE STUDY WAS CONDUCTED.